2015
DOI: 10.1007/s10772-015-9327-z
|View full text |Cite
|
Sign up to set email alerts
|

Automatic prosodic tone choice classification with Brazil’s intonation model

Abstract: This paper examines the performance of automatically classifying five tone choices (i.e., falling, rising, rising-falling, falling-rising, and neutral) of Brazil's intonation model. We tested two machine learning classifiers (neural network and boosting ensemble) in two configurations (multi-class and pairwise coupling) and a rule-based classifier. Three sets of acoustic features built from the TILT and Bézier pitch contour models and a new four-point pitch contour model we introduced here were investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The problem of prosodic similarity evaluation arises within multiple research areas including automatic tone classification [44] and proficiency assessment [45]. Although in [46] it was shown that the difference between two given pitch contours may be perfectly grasped by Pearson correlation coefficient (PCC) and Root Mean Square (RMS), in the last two decades, prosodic similarities were successfully evaluated using dynamic time warping (DTW).…”
mentioning
confidence: 99%
“…The problem of prosodic similarity evaluation arises within multiple research areas including automatic tone classification [44] and proficiency assessment [45]. Although in [46] it was shown that the difference between two given pitch contours may be perfectly grasped by Pearson correlation coefficient (PCC) and Root Mean Square (RMS), in the last two decades, prosodic similarities were successfully evaluated using dynamic time warping (DTW).…”
mentioning
confidence: 99%
“…Next, the rise and fall amplitudes are computed for each segmented verse. These parameters represent the strength of voice conveyed through a verse [38,39].…”
Section: Tilt-based Tarannum Shape Labelingmentioning
confidence: 99%
“…Similarly, the computer employed a number of supervised machine learning classifiers to evaluate the pitch contours of the prominent syllables to ascertain their tone choice (Johnson & Kang, 2015b). The same combinations of the Analyst X annotated TIMIT and BURNC corpora, which were drawn on to test and train the prominent syllable classifiers, were also made use of in testing and training the tone choice classifiers.…”
Section: Computer Annotationmentioning
confidence: 99%